Relationship Social Media Activities with Adolescent Psychosocial at Junior High School 1 Damai City, Districts Damai - Agustinus Ding (Rifa'Institute, 2023)
Introduction: Psychosocial problems in adolescents are also influenced by factors of internet activity (social media). Teens who actively play social media, namely 87% and 33.3% of those who have smartphones are teenagers who are addicted to smartphones and these teens show high levels of depression, anxiety, stress, and poor sleep quality. Objective: to know relationship social media activities with adolescent psychosocial at One Junior High School 1 Damai City Districts Damai. Method: The research design in this study was descriptive correlation using a cross-sectional approach. The study was conducted in February-April 2022. The statistical test used is Chi-Square if it is obtained t count (p-value) <0.05, then the hypothesis Ha is accepted and Ho is rejected. Result and Discussion: Relationship of social media activity with psychosocial (pValue = 0.00). Activities using social media at Junior High School 1 Damai City Districts Damai are in the low category (59.2%). Psychosocial adolescent at Junior High School 1 Damai City Districts Damai in good category (35.9%). Conclusion: there is a relationship between social media activities with adolescent psychosocial at Junior High School 1 Damai City, Districts Damai.